Combination activity of antibiotics and herbal formulations against select bacterial pathogenic organisms - Nwanekwu, Kenneth Emeka (Technium BioChemMed, 2021)
The antibacterial activity of some commercial herbal medicine preparation in combination with antibiotics against five Gram positive and negative bacteria were studied using the agar diffusion method. The herbal medicines namely Alomo bitters, Goko cleanser, Chimason mighty and Yoyo bitters and the antibiotics; Ampicillin, Cloxacillin, Chloramphenicol and Tetracycline were tested alone against the test organisms Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Salmonella sp and Shigella sp. Alomo bitters and Goko cleanser were selected and tested in combination with all four antibiotics against the organisms. The result shows that individually, both the herbal medicine and antibiotics demonstrated varying levels of antibacterial activity with recorded diameter zones of inhibition ranging from 0 to 35mm. While the combination of the two most active herbal medicines (Alomo bitters and Goko cleanser) with the antibiotics showed both a positive and negative drug-herb interactions and an indifference. Alomo bitters and antibiotics gave a 45% positive interaction, 15% negative interaction and 40% non-interaction or indifference. While Goko cleanser and antibiotics gave a 65% positive interaction, 10% negative interaction and 25 % non-interaction or indifference. This shows that herbal medicine preparations and antibiotics may be used in combination and complementary medicines in the fight against infectious microbial diseases.